ANALISIS PENGARUH CASH FLOW, FUND SIZE, FAMILY SIZE, EXPENSE RATIO, STOCK SELECTION ABILITY DAN LOAD FEE TERHADAP KINERJA REKSADANA SAHAM PERIODE 2012-2014 - Nursyabani, Paramitha Azizah; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2016)
Mutual Fund is one of investment that raise funds from the investor to be invested in a portofolio of securities and managed by an investment manager in accordance with the investment objectives.This study was conducted to determine the effect of cash flow, fund size, family size, expense ratio, stock selection ability and load fee on the performance of mutual fund. The data used in this study are NAV,BI Rate, expense ratio, load fee and total NAV investment manager of 45 mutual funds in 2012-2014 period.The method that used is multiple reggresion analysis with clasical assumption by using a normality test, autocorrelation test, heteroscedasticity test, and mulitcollinearity test. The method that used for testing the hypothesis are the F-test and t test. The result of this test showed partially cash flow and stock selection ability have a positive significant effect on the performance of mutual funds. Expense ratio and load fee have negative significant effect on the performance of mutual fund. While the fund size and family size have postive effect but not significant on the performance of mutual fund. Based on the result Adjusted R Square , the R value of 0.318 which means the 31,8% achievement of mutual fund performance can be explained by cash flow, fund size, fund family size, expense ratio, stock selection ability and load fee.